A frequent acoustic sign of speech motor delay (SMD). - Shriberg, Lawrence D.; Wren, Yvonne E. (Clinical Linguistics & Phonetics, 2019)
Recent studies report prevalence, phenotype, and persistence findings for a paediatric motor speech disorder in addition to childhood dysarthria and childhood apraxia of speech termed Speech Motor Delay (SMD). The aim of the present study was to determine if there is a frequent acoustic sign of SMD, with implications for theory, assessment, and treatment. We examined the frequency of 19 acoustic signs of SMD in audio recordings of continuous speech and word-imitation tasks in three groups of speakers with SMD: 50 children (mean age 5.1 years) with idiopathic Speech Delay (SD) from 6 USA cities; 87 children, adolescents, and adults with eight types of complex neurodevelopmental disorders; and 9 children (mean age 8.8 years) with persistent idiopathic SD from a population-based study of children in the South West of England. The 19 acoustic signs of imprecise or unstable speech, prosody, and voice were standardized on typical speakers of the appropriate dialect. The criterion for a frequent acoustic sign was that it occurred in at least 50% of participants with SMD in each of the three groups. Findings indicated that lengthened mid-vowels and diphthongs was the one sign that met criteria, occurring in 64.4% of the 146 participants with SMD, including 71% of the 87 participants with complex neurodevelopmental disorders. Findings are interpreted to support the potential of this acoustic sign, and possibly several others associated with temporal dimensions of speech sound development, to inform explication of the neuromotor substrates of SMD.